2021
DOI: 10.1063/1674-0068/cjcp2008151
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics and electronic properties of Heusler alloys Li2AlX (X=Ga, In): A comparison study

Abstract: The lattice parameters, bulk modulus, first derivative of the bulk modulus, electronic band structures, phonon dispersion curves and phonon density of states calculations for Li2AlGa and Li2AlIn Heusler alloys are performed and compared in this study using density functional theory within the generalized gradient approximation. Computed lattice parameters display a good agreement with the literature. Obtained electronic band structures of both Heusler alloys show that they are in semi-metallic structure. Phono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Two modes with a lower energy value are transverse acoustic (TA) modes, and one mode with a higher energy value is longitudinal acoustic (LA) 42 . Moreover, optical modes with lower energy values in each branch are transverse optical (TO) modes, while modes with higher energy values in each branch are longitudinal optical (LO) modes 1 . It can be seen from Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two modes with a lower energy value are transverse acoustic (TA) modes, and one mode with a higher energy value is longitudinal acoustic (LA) 42 . Moreover, optical modes with lower energy values in each branch are transverse optical (TO) modes, while modes with higher energy values in each branch are longitudinal optical (LO) modes 1 . It can be seen from Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Heusler discovered the first alloy of the Heusler type, Cu 2 MnAl, in 1903 1 . However, since Heusler compounds are made up of non-ferromagnetic materials, their interesting ferromagnetism has kept them a scientific wonder for a long time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jolayemi et al (2021) determined the thermoelectric properties of LiAlSi crystal using Boltzmann transport theory and DFT. Dogan & Gulebaglan (2021b) examined and compared the electronic and dynamic properties of Li2AlIn and Li2AlGa materials in the Heusler structure. Shah et al (2018) demonstrated optoelectronic and transport properties of semiconductor LiBZ (B = Al, In, Ga and Z = Si, Ge, Sn) crystals.…”
Section: Introductionmentioning
confidence: 99%